Implementation of the Numbered Head Together (NHT) model based on interactive multimedia ispring suite 10 on the subject of work and energy to improve student understanding - Nurjanah, Elis; Adimayuda, Rizal (Insitut Pendidikan Indonesia, 2023)
With the development of time, educators are required to continuously innovate in the use of models, media, and other learning aspects that support the learning process. This demand is further heightened as students are now required to have 21st-century skills. The aim of this research is to determine the improvement in students’ understanding of the topic of Work and Energy by using the Numbered Head Together (NHT) learning model based on interactive multimedia iSpring Suite 10. This study uses a quantitative pre-experimental research method, employing a one-group pretest-posttest design. Sample selection was conducted using purposive sampling, which involves selecting samples based on specific considerations. The sample for this research was a tenth-grade class in one of the high schools in Indonesia. The research instruments used were a 20-item multiple-choice test and a response questionnaire. Based on the test results, the average N-Gain value obtained was 0.41, categorizing it as a moderate improvement according to the N-Gain criteria. Therefore, it can be concluded that there is an improvement in students’ understanding of the concepts of work and energy when using the NHT learning model based on interactive multimedia iSpring Suite 10.